An integrated in vivo/in vitro framework to enhance cell-free biosynthesis with metabolically rewired yeast extracts - Blake J. Rasor (Nature Portfolio, 2021)
Cell-free systems enable the design of biosynthetic pathways for sustainable chemical synthesis. Here the authors create an integrated framework for accelerating design using extracts from genetically rewired strains.